2022
DOI: 10.3390/ph15080920
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase 2 as a Pharmacological Target in Heart Failure

Abstract: Heart failure (HF) is an acute or chronic clinical syndrome that results in a decrease in cardiac output and an increase in intracardiac pressure at rest or upon exertion. The pathophysiology of HF is heterogeneous and results from an initial harmful event in the heart that promotes neurohormonal changes such as autonomic dysfunction and activation of the renin-angiotensin-aldosterone system, endothelial dysfunction, and inflammation. Cardiac remodeling occurs, which is associated with degradation and disorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 115 publications
1
14
0
Order By: Relevance
“…Baraibar-Churio et al showed that the MMP-10 deficiency causes chronic inflammation in the cardiac and skeletal muscles in aged mdx mice [ 71 ]; thus, suggesting it as a critical therapeutic targe for muscular dystrophy. MMP-2 activity is enhanced in the muscles [ 96 ], and TIMP-1 is increased in the serum and plasma of muscular dystrophy patients [ 97 ]. MMP-10 deficiency has been linked with the progression of severe muscular dystrophy in aged dystrophic mice [ 71 ].…”
Section: Function Of Mmps In Musculoskeletal Diseasesmentioning
confidence: 99%
“…Baraibar-Churio et al showed that the MMP-10 deficiency causes chronic inflammation in the cardiac and skeletal muscles in aged mdx mice [ 71 ]; thus, suggesting it as a critical therapeutic targe for muscular dystrophy. MMP-2 activity is enhanced in the muscles [ 96 ], and TIMP-1 is increased in the serum and plasma of muscular dystrophy patients [ 97 ]. MMP-10 deficiency has been linked with the progression of severe muscular dystrophy in aged dystrophic mice [ 71 ].…”
Section: Function Of Mmps In Musculoskeletal Diseasesmentioning
confidence: 99%
“…In I/R injury, expression of MMP-2 is of particular interest because MMP-2 degrades extracellular matrix substrates including Type IV collagen, laminin, elastin, interstitial fibrillar collagen, and sarcomeric proteins [ 35 , 36 ]. The expression of this zinc-dependent protease is regulated by mechanical signals, inflammatory factors, hormones, and NPs, among other factors; some authors even suggest that MMP-2 can be used as a possible pharmacological target in the treatment of heart failure [ 31 , 36 , 37 , 38 ]. Therefore, we analyzed the expression of MMP-2 in all experimental groups and found that the expression of this enzyme was higher in hearts from MetS rats in sham-operated conditions and under I/R damage without there being changes in the Ct group.…”
Section: Discussionmentioning
confidence: 99%
“…Ang II stimulates MMP expression in advanced atherosclerotic lesions 43 . MMP2, which is mainly derived from arterial endothelial cells, is one of the most abundant proteases in cardiomyocytes and is considered a biomarker for heart failure and acute coronary syndrome 44,45 . MMP2 mediates Ang II‐induced vascular injury by triggering inflammatory and immune responses and participates in various processes such as ECM degradation, thrombosis and atherosclerotic rupture 46,47 .…”
Section: Discussionmentioning
confidence: 99%